I am Ozzy - Osbourne, Ozzy, frey50; Ayres, Chris, 1975- (New York : Grand Central Pub., 2010)
One of television's best loved personalities via the wildly successful hit MTV show The Osbournes, Ozzy tells about his days on the road and the heartbreak he suffered during those days of hard living.
In the beginning... John the burglar ; Ozzy Zig needs gig ; The witch and the Nazi ; "You guys ain't black!" ; Killing the Vicar (In Atrocity Cottage) ; The end is nigh -- Starting over. Des Moines ; While I was sleeping ; Betty, where's the bar? ; Blackout ; Dead again -- Patient notes.
Keywords: Osbourne, Ozzy, -- 1948-; Rock musicians -- United States